NAVIGATING UNCERTAINTY: CHALLENGES OF TEACHER PROFESSIONAL DEVELOPMENT FOR EYL IN INDONESIA - Budiarti, Litani Ika; Widhiyanto, Widhiyanto; Andika, Jeffri Dian (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The status of English as an optional subject in the Indonesian primary school curriculum has created significant ambiguity for English for Young Learners (EYL) teachers. This policy uncertainty limits institutional support and curricular guidance, leaving many EYL teachers without a clear framework to effectively deliver English Language Teaching (ELT) at the primary level. This study employs a Systematic Literature Review (SLR) to examine the landscape of Teacher Professional Development (TPD) initiatives for EYL educators in Indonesia. Drawing from peer-reviewed journals, government documents, and educational reports published between 2020-2025, this review identifies key themes, challenges, and best practices in the professional development of EYL teachers. The findings reveal that while various TPD programs exist, many are fragmented, underfunded, or misaligned with the practical needs of teachers operating in contexts where English instruction lacks formal curricular status. This article highlights the urgent need for policy-informed, context-responsive TPD models to equip EYL teachers with the practical needs of teachers operating in contexts where English instruction lacks formal curricular status.